PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PADA CV. ZAM ZAM HONDA MOTOR LUBUK JAMBI KABUPATEN KUANTAN SINGINGI - ", Maria; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The research to find out how the influence of the marketing mix on purchasing decisions in order to achieve sales targets planned by CV. Zam Zam Honda Motorand also to find out purchasing decisions in making purchases. The population in this study were consumers of CV. Zam Zam Honda Motor by taking as many as 100 respondents using the census method. Research data in the form of primary data with a questionnaire as a research instrument and secondary in the form of company archives. Analysis of the data used is by using statistical analysis with the help of the SPSS program. Based on the results of research conducted the authors draw conclusions on the marketing mix influence on purchasing decisions on CV. Zam Zam Honda Motor from the responses of the respondents studied that each has indicators that are interrelated and influence the purchasing decisions on CV. Zam Zam Honda Motor.Keywords: marketing mix, purchasing decisions